How to lengthen the nuclear fuse. - Feiveson, H.A.
Presidents Clinton and Yeltsin took a step toward de-alerting strategic nuclear forces in 1994, when they pledged to stop aiming strategic missiles at each other's country. But the pact was symbolic only. The missiles retained their wartime targets in computer memory, and the target coordinates could be reloaded into the missile guidance computers within seconds. If either President ordered a missile attack, the message would be transmitted in seconds to land-based launch crews and in minutes to submarine crews. Thousands of warheads could be launched within 30 minutes or so of the initial decision. A stand-down from this strategic forces alert-a lengthening of the launch readiness of the missiles from minutes to hours or days or longer-would do in reality what the de-targeting step did symbolically. It would end an anachronistic state of affairs-the fact that, a decade after the end of the Cold War, the United States and Russia are still maintaining nuclear weapons on hair-trigger alert aimed at each other's nuclear forces and cities. The authors discuss the alert status of the nuclear forces, pressure for fast launches, and the path to de-alerting, and a de-alerting scenario
Keywords: Launch readiness lengthening; Missile guidance computers; Strategic forces alert; Strategic missiles; Strategic nuclear forces de-alerting.; Target coordinates; Wartime targets